2014
DOI: 10.1002/tox.22052
|View full text |Cite
|
Sign up to set email alerts
|

Edaravone attenuates brain damage in rats after acute CO poisoning through inhibiting apoptosis and oxidative stress

Abstract: Acute carbon monoxide (CO) poisoning is the most common cause of death from poisoning all over the world and may result in neuropathologic and neurophysiologic changes. Acute brain damage and delayed encephalopathy are the most serious complication, yet their pathogenesis is poorly understood. The present study aimed to evaluate the neuroprotective effects of Edaravone against apoptosis and oxidative stress after acute CO poisoning. The rat model of CO poisoning was established in a hyperbaric oxygen chamber b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Notably, preventive effect of antioxidants such as vitamin supplements and N-acetylcysteine on bone loss has been reported before (29,30). It is found that Edaravone has neuroprotective influence on cerebral ischemia by increasing the basal expressions of HO-1 and Nrf-2 proteins, which are two important antioxidative stress proteins in tissues and cells (31). Additionally, Edaravone has antiapoptosis abilities.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, preventive effect of antioxidants such as vitamin supplements and N-acetylcysteine on bone loss has been reported before (29,30). It is found that Edaravone has neuroprotective influence on cerebral ischemia by increasing the basal expressions of HO-1 and Nrf-2 proteins, which are two important antioxidative stress proteins in tissues and cells (31). Additionally, Edaravone has antiapoptosis abilities.…”
Section: Discussionmentioning
confidence: 96%
“…Edaravone has been reported to protect lung isolated mitochondria against ROS generation and mitochondrial dysfunction induced by the toxin Paraquat (PQ) [18]. Notably, a previous study found that edaravone improves mitochondrial function and reduces apoptosis by modulating mitochondria-dependent apoptosis pathways [19]. .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study indicated that the significantly ultrastructural alterations occurred in brain parenchyma in rats after CO exposure, including brain edema, chromatin condensation, nucleus membrane and cell organelles decomposition, even neuronal death (Li Q. et al, 2015; Li et al, 2016). N -butylphthalide (NBP), a new drug extracted from celery seeds (see Figure 1 ), was approved by China Food and Drug Administration in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, NBP had also positive effects in stabilizing the NVUs and improving the neurological deficits through its primary target vascular endothelium (Li et al, 2007; Thored et al, 2007). Besides, the application of NBP could inhibit neuronal apoptosis, and attenuate brain parenchymal injury induced by CO poisoning (Li et al, 2016). Nevertheless, the effects of NBP on the ultrastructural integrity and on the BBB after CO poisoning are still unknown.…”
Section: Introductionmentioning
confidence: 99%